The implementation of dhikr taskiyatun nafs in enhancing the spiritual intelligence of takhasus class students at pondok pesantren Nurul Ikhlas Sepande Candi Sidoarjo - Oktafiawan, Angga Dwi; El Yunusi, Muhammad Yusron (Privietlab, 2026)
This study examines the implementation of dhikr taskiyatun nafs in enhancing the spiritual intelligence of takhasus class students at Pondok Pesantren Nurul Ikhlas Sepande Candi Sidoarjo. The research employs a qualitative descriptive approach using field research methods. Data were collected through participatory observation, in depth interviews with ustadz and students, and institutional document analysis. The study aims to explore the institutional configuration, implementation mechanism, and transformative impact of dhikr taskiyatun nafs on students’ spiritual development. The findings reveal that dhikr taskiyatun nafs has been systematically institutionalized since the establishment of the pesantren and functions as a central instrument of spiritual formation. Its implementation follows a structured pedagogical process, including the internalization of dhikr recitations, routine repetition in guided assemblies, deepening of theological meaning, and integration into daily life practices. The practice is supported by continuous supervision and spiritual mentoring by the kiai and ustadz. The results indicate significant transformation in students’ spiritual intelligence, reflected in increased reflective self awareness, strengthened transcendental relationship with Allah, improved emotional stability, and enhanced moral behavior. Students reported experiencing greater inner peace, patience, and consistency in worship practices. In conclusion, dhikr taskiyatun nafs serves not merely as a ritual activity but as a systematic spiritual mentoring model that contributes to the holistic development of students’ spiritual intelligence within the pesantren educational context.